2016
DOI: 10.1001/jama.2016.1961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on Tibial Cartilage Volume and Knee Pain Among Patients With Symptomatic Knee Osteoarthritis

Abstract: IMPORTANCE Observational studies suggest that vitamin D supplementation is associated with benefits for knee osteoarthritis, but current trial evidence is contradictory.OBJECTIVE To compare the effects of vitamin D supplementation vs placebo on knee pain and knee cartilage volume in patients with symptomatic knee osteoarthritis and low vitamin D levels. DESIGN, SETTING, AND PARTICIPANTSA multicenter randomized, double-blind, placebo-controlled clinical trial in Tasmania and Victoria, Australia. Participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 35 publications
4
139
0
4
Order By: Relevance
“…Indeed, previous studies have shown an inverse correlation between 25(OH)D concentrations and LDL cholesterol with an independent effect of solar UV radiation (32 (39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, previous studies have shown an inverse correlation between 25(OH)D concentrations and LDL cholesterol with an independent effect of solar UV radiation (32 (39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 95%
“…A 2-year randomized controlled trial in which 413 participants were given monthly treatments with oral vitamin D showed that oral supplementation did not produce significant clinical or cartilage volume structural differences in patients who were previously vitamin D deficient. 25 In a double-blind, randomized placebo-controlled trial, Arden et al 4 also showed that there was no significant difference in the rate of joint space narrowing in the medial compartment of knees due to vitamin D supplementation.…”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%
“…Пацієнти з гонартрозом і низьким рівнем 25(OH)D (12,5-60 нмоль/л) протягом 2 років отримували щомісячно перорально 50 000 МО віта-міну D [58]. Група пацієнтів, що отримувала плацебо, служила контролем.…”
Section: фактори ризику дефіциту вітаміну D і розвиток патології на тunclassified